Financial Soundness in Indian Life Insurance: A Comparison Between Two Leading Private Players - Sinha, Abhijit (Indian Journal of Finance, 2013)
The author has made a study on the life insurance sector in India. The main purpose of this analytical study was to understand the level of soundness of the life insurers - Bajaj Allianz Life Insurance and ICICI Prudential Life Insurance - chosen as the sample for the purpose of the present research. The methodology applied is the CARAMELS framework developed by the International Monetary Fund to understand financial strengths and weaknesses of different sectors like banking, insurance etc. In fact, the CARAMELS model acts as a framework which considers different parameters for determining the soundness of organizations spread across different industries. The study on ICICI Prudential Life Insurance and Bajaj Allianz Life Insurance gave mixed results. Several areas have been identified which require a lot of improvement. This study is one of the unique studies on the financial soundness aspect in the insurance sector.